2023
DOI: 10.3389/fpubh.2023.1228920
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories in physical functioning at older age in relation to childhood and adulthood SES and social mobility: a population-based cohort study

Andrzej Pająk,
Maciej Polak,
Magdalena Kozela
et al.

Abstract: IntroductionOlder age is associated with the deterioration of physical functioning (PF), and low PF is strongly related to poor quality of life among older people. We conducted a study to examine the trajectories of PF between middle and old age, considering sex differences as well as the association between socioeconomic status (SES) at different life stages and changes in PF.MethodsWe analyzed data from the Polish arm of the HAPIEE (Health, Alcohol and Psychosocial factors In Eastern Europe) study, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Park et al [ 27 ], on the other hand, found SES to have an impact on the sex differences in physical functioning among older adults, although they defined physical functioning as having limitations in ADL (i.e., basic needs such as eating, getting dressed, hygiene [ 45 ]) and instrumental ADL (IADL, i.e., shopping, doing housework, financial tasks [ 46 ]). Pajak et al [ 47 ] also found SES to be statistically significantly positively associated with physical functioning in their study of the 45 to 65-year-old Polish population. They also used the Physical Functioning Scale from SF-36 and showed that the social gradient regarding physical functioning was larger in women than in men.…”
Section: Discussionmentioning
confidence: 89%
“…Park et al [ 27 ], on the other hand, found SES to have an impact on the sex differences in physical functioning among older adults, although they defined physical functioning as having limitations in ADL (i.e., basic needs such as eating, getting dressed, hygiene [ 45 ]) and instrumental ADL (IADL, i.e., shopping, doing housework, financial tasks [ 46 ]). Pajak et al [ 47 ] also found SES to be statistically significantly positively associated with physical functioning in their study of the 45 to 65-year-old Polish population. They also used the Physical Functioning Scale from SF-36 and showed that the social gradient regarding physical functioning was larger in women than in men.…”
Section: Discussionmentioning
confidence: 89%